A Preliminary Thought on the Transitory Nature of First-year Architecture Students in UiTM Cawangan Sarawak. - Hashim, Mohd Iqbal; Husaini, Nur Atiqah; Sebri, Nur Izzati (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the transitional challenges that first-year architecture students face at UiTM Cawangan Sarawak, transitioning from layperson to systematic architectural design thinking. Grounded in postcolonial theory and the political economy of space, the research explores how colonial-capitalist ideology is perpetuated in historical pedagogical structures, engendering problems in students' production of creative works. Observations during tutorials and critiques reveal that students often assume passive roles, resulting in the underutilisation of design archetypes in their creative expressions. The study addresses two primary objectives: (1) to evaluate students’ reflections on their experiences during tutorial and critique sessions, and (2) to define and reflect on the problem of the transitory nature of the first-year architecture programme. The paper identifies incongruities between field experts and laypersons as the central issue through a mixed-methods approach, combining post-activity surveys, student evaluations, and literature reviews. The outcomes provide fundamental insights into a problem of definition in the first-year architecture programme. By situating the study within the broader discourse of inclusive education, this paper calls for a study that views the problem from the perspective of the tutors and, consequently, their teaching and learning approach as the central inquiry. This paper contributes to the ongoing dialogue on innovation in architectural pedagogy, emphasising a fundamental shift in the discourse towards the core of teaching and learning: the dynamic of teaching and learning.